Peningkatan Skill Santri Melalui Pemanfaatan Kain Bekas Menjadi Barang Bernilai Guna Berupa Keset di Pondok Pesantren Miftahul Mubtadiin Al-Ridlo Krempyang Tanjunganom Nganjuk - Abdul Kholiq; Idam Mustofa (Janaka, Jurnal Pengabdian Masyarakat, 2021)
One of the problems in the boarding school environment is that the number of clothes that are no longer suitable for use is left alone, this motivates us to be able to use these unused clothes to become valuable materials in the form of doormats, so that the problem of clothing which is an endless problem at the pesantren is minimized a little. and can be used for useful things. These used clothes are assets that can be used to develop the creativity of the students and provide insight into entrepreneurship, not only oriented to science, but also to creativity, innovation and skill development of the students. In the future, we hope that this program can help assisted partners in terms of managing used clothes and can increase the creativity of these students. In its implementation, we use the Service Learning method, in order to pay attention to the environment and to be able to solve problems that often occur among cleaning workers, which have been a burden for them.